IL-38 attenuates renal ischemia/reperfusion injury through suppressing inflammation in mice: IL-38 attenuates renal injury - Liang, Decui; Dai, Lanxiang; Sun, Hao; Li, Linlin (Cellular and Molecular Biology, 2025)
Inflammation plays an important role in the pathogenesis of renal ischemia/reperfusion injury (IRI). Interleukin-38 (IL-38) is an emerging cytokine with multiple functions involved in infection and immunity. The present study aimed to determine whether IL-38 attenuates renal IR injury in an animal model and to identify the underlying mechanisms. For this purpose, the renal IRI model was induced by left renal pedicle clamping for 45 min and right nephrectomy in mice. All mice were intraperitoneally injected with vehicle or IL-38. Renal histology, function, apoptosis and inflammatory cytokines were assessed. mRNAs were detected by Real-time PCR. The proteins were measured by Western blot. Results showed that the expression of IL-38 mRNA and protein in kidney tissue was significantly increased at 6 h and reached a peak at 24 h after renal IRI, along with the kidney dysfunction. IL-38 significantly decreased renal IRI, as reflected by the attenuation of renal dysfunction, tubular damage and cellular apoptosis. Thus, IL-38 markedly ameliorated the survival rate after renal IRI. In addition, IL-38 significantly increased the level of cytoplasmic IκB-α and suppressed the nuclear translocation of NF-κB, which inhibited the expression and release of inflammatory cytokines. In conclusion, IL-38 significantly protects against renal IRI probably by inhibiting pro-inflammatory reactions.